P3-4-9. Muscle ultrasonographic detection of fasciculation in patients with amyotrophic lateral sclerosis. Issue 5 (May 2018) - Aoe, Yasutaka; Sato, Kengo; Ogawa, Ayame; Onda, Kanna; Matsuura, Yuka; Oguri, Masayoshi; Watanabe, Yasuhiro; Hanajima, Ritsuko; Hirooka, Yasuaki
Abstract : Muscle ultrasonography is reported to be useful for detection of fasciculation. We examined whether muscle ultrasonography is an effective diagnostic tool of amyotrophic lateral sclerosis (ALS). Analysis was performed in 17 patients with ALS or motor neuron disease. An Aplio XG ultrasonography device and a 7.5-MHz linear probe were used to observe 11 muscles for 20 s to determine the presence or absence of fasciculation. The overall fasciculation positive rate was 68.5%, and it was higher in the limbs. Fasciculation was much more frequently detected on ultrasonography than on needle electromyography (biceps brachii: 87% vs 73%, quadriceps: 86% vs 43%, and tibialis anterior: 89% vs 33%). In measurement using the M-mode of ultrasonography, the duration of fasciculation was varied from 0.1 to 0.5 s, appearing aperiodically. Its duration tended to be short at the tongue. The muscle length and volume probably caused of several durations of fasciculation. When the diagnostic grade was high, the number of fasciculations tended to increase (definite: 7.0/20 s, probable: 4.5/20 s, and possible: 3.7/20 s). Therefore, the number of fasciculations may be related to disease progression. In conclusion, muscle ultrasonography may be useful for diagnosis of ALS.